Determination of the profile of antibiotic resistance of Salmonella enterica isolated from pigs in a slaughterhouse in Lima, Peru - Ríos C., Arnold (2019)
The aim of this study was to determine the profile of antibiotic resistance of isolated Salmonella enterica strains during the slaughtering process of pigs in a slaughterhouse in Lima. Strains of Salmonella enterica (n=148) isolated from stool samples and mesenteric ganglia of pigs were used. The evaluation of antibiotic resistance was performed by the disc diffusion method (Kirby-Bauer). Thirteen antibiotics of frequent use in human medicine were considered, of which most of them are also used in pigs as prophylactic and growth promoters. All strains showed resistance to tetracycline and all showed sensitivity to ciprofloxacin. Likewise, all strains were resistant to at least one antibiotic.